The Testing of Belief-Adjustment Model and Framing Effect on Non-Professional Investor’s Investment Decision-Making - Taufan Hanafi (Universitas Hayam Wuruk Perbanas, 2017)
This study aims to find out the effect of belief-adjustment model and framing effect on non-professional investor’s investment decision making. The designs of experiment used in this study are the presentation pattern of 2x2x2, disclosure pattern (step-by-step and end-of-sequence), disclosure evidence of information order (good news followed by bad news and bad news followed by good news), and framing effect (framing condition according to the information and framing condition with the reversed information). The research hypotheses in this study are tested using parametric test. The dependent variable used in this study is investment decision making, while, the independent variables used in this study are belief-adjustment model and framing effect. The number of participants involved in this study is 80 undergraduate students of STIE Perbanas Surabaya majoring in Accounting or Management. The results indicate that there are significant differences in decision making and recency effect occurs between the investors who receive good news followed by bad news and the investors who receive bad news followed by good news in the step-by-step disclosure pattern with framing condition according to the information. The results of this study also show that primacy effect occurs between the investors who receive good news followed by bad news and the investors who receive bad news followed by good news in the step-by-step disclosure pattern with framing condition in reversed information.